2011
DOI: 10.1093/jnci/djr283
|View full text |Cite
|
Sign up to set email alerts
|

Persistence of Type-Specific Human Papillomavirus Infection and Increased Long-term Risk of Cervical Cancer

Abstract: HPV negativity was associated with a very low long-term risk of cervical cancer. Persistent detection of HPV among cytologically normal women greatly increased risk. Thus, it is useful to perform repeated HPV testing following an initial positive test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
144
2
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 156 publications
(162 citation statements)
references
References 28 publications
12
144
2
4
Order By: Relevance
“…Similar to our findings, a study of U.S. women in New Mexico showed significantly lower proportions of CIN2þ attributable to HPV16/18 in Hispanics compared with non-Hispanic whites (17). It is important to caution against extrapolating results from studies of CIN2þ to make inferences about HPV types detected in cervical cancer because only about 30% of CIN2þ lesions could progress to invasive cancer and those that are attributable to HPV16/18 have a much higher likelihood of progression compared with lesions due to other high-risk types (4,26,27). A population-based U.S. study using data from state-based cancer registries found that HPV16/18 are attributable to the same proportion (67%) of invasive cervical cancers in non-Hispanic white and non-Hispanic black women (28).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to our findings, a study of U.S. women in New Mexico showed significantly lower proportions of CIN2þ attributable to HPV16/18 in Hispanics compared with non-Hispanic whites (17). It is important to caution against extrapolating results from studies of CIN2þ to make inferences about HPV types detected in cervical cancer because only about 30% of CIN2þ lesions could progress to invasive cancer and those that are attributable to HPV16/18 have a much higher likelihood of progression compared with lesions due to other high-risk types (4,26,27). A population-based U.S. study using data from state-based cancer registries found that HPV16/18 are attributable to the same proportion (67%) of invasive cervical cancers in non-Hispanic white and non-Hispanic black women (28).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that persistent detection of high-risk HPV among cytologically normal women drastically increases their risk of future CC. [21][22][23] Therefore, HPV prevalence in older women is more indicative of actual CC risk.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical cancer is the second most prevalent disease worldwide occurrence with new cases every year and approximately 80% of them reported in developing countries (Munoz et al, 2003;Parkin and Bray, 2006;Lin et al, 2008;Chen et al, 2011 and. Such type of cases appears mainly in between the age of 30 and 50.…”
Section: Introductionmentioning
confidence: 99%